Studying the role of cognitive control in reasoning: evidence for the congruency sequence effect in the ratio-bias task. (2nd January 2017) - Aczel, Balazs; Palfi, Bence
ABSTRACT: In this study, we investigated whether control of the conflict between incongruent heuristic and analytical answer options in a reasoning task is modulated by the presence of conflict on previous trials. In two experiments, we found that the incongruency of the previous trial has a significant effect on the control exhibited on the current trial. Our data also showed that this adaptation effect is modulated by the incongruency of the previous series of trials. These results demonstrate the same control adaptation effects for a reasoning task as observed for standard response interference tasks. Coinciding control effects in the two research areas suggest that cognitive control might be an important mechanism underlying performance on reasoning tasks. Based on these results we argue that the study of cognitive control in reasoning could potentially facilitate the refinement of empirical predictions and provide a new tool to explore the exertion of top-down control in human thinking.